Resistance to thiabendazole in Fusarium species and Helminthosporium solani in potato tubers treated commercially in eastern Canada - Platt, H.W. (Phytoprotection, 1997)
During the 1992-1993 and 1994-1995 winter storage period for potatoes (Solarium tuberosum) in Quebec, New Brunswick, and Prince-Edward-Island, tubers were collected which had symptoms of fusarium tuber rot and silver scurf and which had been treated commercially after harvest with thiabendazole. Resistance to thiabendazole was detected in isolates of Fusarium sambucinum and Helminthosporium solani but not in isolates of F. avenaceum and F. oxysporum. However, the majority of those farms surveyed (64%) had adequate disease control with no pathogen isolated from the diseased tubers. Incidence and EC50 values of resistant isolates were lower than found elsewhere and the occurrence of farms with resistant isolates of F. sambucinum (18%) was greater than for H. solani (7%). For H. solani, EC50 values of resistant isolates were substantially less than those found in Alberta. While the study investigated commercial operations employing a wide range of thiabendazole rates (6-42 g a.i. t-1), no specifie trends were detected between the occurrence of resistant isolates and cultivar or thiabendazole application rate.